Пародийное в творчестве Владимира Шинкарева - Paulus, Jędrzej Melchior (Studia Rossica Posnaniensia, 2015)
Vladimir Shinkarev is a famous Russian writer and painter. His Mitki and Maxim and Fedor were among the most popular underground books in Leningrad in the late 1980s. This article is devoted to studying both of these famous texts and represents an attempt to find a parody of other books or of Japanese culture. The author also analyzes Shinkarev’s literature and religious parodies in the Soviet context.